Multifunctional liquid crystal polymer network soft actuators. Issue 6 (27th January 2020) - Yu, Li; Peng, Ran; Rivers, Geoffrey; Zhang, Che; Si, Pengxiang; Zhao, Boxin
Abstract : Multifunctional liquid metal/liquid crystal polymer network soft actuators combine ultrahigh conductivity and thermal-responsive actuation behavior under large strain. Abstract : Multifunctionality is an essential feature for the application of soft actuators in the fields of soft robotics, flexible electronics, and energy generators. Accordingly, liquid crystal polymer networks (LCNs) afford a promising platform for designing multifunctional soft actuators due to their reversible, programmable, and multi-stimuli-responsive shape changing behaviors via the self-organization of liquid crystals. Although the introduction of functional components ( e.g. conductive and magnetic fillers) has been considered to be an effective approach to exploit multifunctional LCN soft actuators, it remains a great challenge to integrate a particular role of functional components while maintaining inherent shape changing capabilities of LCNs. Herein, we report a facile method to achieve multifunctional LCN soft actuators by directly injecting the desired functional component in the liquid state into LCN tubular actuators. In our design, the LCN tubular actuators prepared via the mechanical programming process act as a structural framework, providing reversible shape changing behaviors with a large strain both in length and inner diameter. To introduce conductive functionality, liquid metals (LMs) are selected as the functional component due to their ultrahigh conductivity and controllable melting point. The multifunctional LCN soft actuators elegantly couple ultrahigh conductivity of the LMs and original shape changing behaviors of the LCN tubular actuators and are demonstrated as a thermal-responsive electrical switch.